The Meaning Of Meaning dalam Teori Lacan - Elya Nindy Alfionita (Jurnal Kajian Seni, 2019)
In this article contains the discourse of understanding of an understanding. Self- understanding when we contemplate quite broad, abstract, and infinite. Not separated from it, the author tries to provide a frame of discussion in this paper, among others; (1.) Discourse of Lacques Jacques (Lacoste), (2.) Language and Significance, (3.) Lacanian and Language Psychoanalysis, (4.) Symbolic Order, (5.) Schizophrenia as Metaphor, (6.) Schizophrenia as Psychoanalysis. The issue discussed in this paper is the discourse of psychoanalytic semiotics and correlates with semiotic philosophy. So the reader understands a science related to philosophy as well as its relation to the truth and beliefs contained in an analysis.